Development of Digital Electronics Practicum Guidance Module with Logisim Applications - Dewantara, Dewi; Azhari, Andy; Sasmita, Fauzia Dwi; Melisa, Melisa; Rusmawati, Ida; Kusuma, Lukman W; Ridho, M Hafiz; Lutfi, M (Unnes Science Education Journal, 2021)
The purpose of this study is to describe the feasibility of the results of the development of the Digital Electronics Practicum Guidance Module with Logisim Applications. Feasibility is seen from the results of the validity, practicality, and effectiveness test of the Digital Electronics Practicum Guidance Module with Logisim Applications. The research subjects were 50 Physics Education Students of Lambung Mangkurat University who took the 2019/2020 Digital Electronics course. The data collection techniques are (1) validity using a validation sheet filled in by the validator; (2) the practicality of using student response questionnaires with indicators of format, quality, clarity, and student interest; (3) effectiveness is seen from the results of student final exams. The results showed that (1) the validity was categorized as good, with a mean score of 3.33; (2) the practicality is in good category, with the mean score of student response is 4.04; (3) the effectiveness of the high category, namely the mean score of students is 79.47. Therefore, it can be concluded that the Digital Electronics Practicum Guidance Module with Logisim Applications is suitable for use in digital electronics practicum.